An Update on Current Antiviral Strategies to Combat Human Cytomegalovirus Infection - Kingshuk Panda; Deepti Parashar; Rajlakshmi Viswanathan (Viruses, 2023)
Human cytomegalovirus (HCMV) remains an essential global concern due to its distinct life cycle, mutations and latency. As HCMV is a herpesvirus, it establishes a lifelong persistence in the host through a chronic state of infection. Immunocompromised individuals are at risk of significant morbidity and mortality from the virus. Until now, no effective vaccine has been developed to combat HCMV infection. Only a few antivirals targeting the different stages of the virus lifecycle and viral enzymes are licensed to manage the infection. Therefore, there is an urgent need to find alternate strategies to combat the infection and manage drug resistance. This review will provide an insight into the clinical and preclinical antiviral approaches, including HCMV antiviral drugs and nucleic acid-based therapeutics.